Development of carbohydrate-based scaffolds for restricted presentation of recognition groups. Extension to divalent ligands and implications for the structure of dimerized receptors - Murphy, PV; Bradley, H; Tosin, M; Pitt, N; Fitzpatrick, GM; Glass, WK (Journal of organic chemistry, 2003)
The solution structure of glycosyl amides has been studied by using NMR. A strong preference is displayed by tertiary aromatic glycosyl amides for E-anti structures in contrast with secondary aromatic glycosyl amides where Z-anti structures predominate. The structural diversity displayed by these classes of molecules would seem to be important as the directional properties of the aromatic ring, or groups attached to the aromatic ring, would be determined by choosing to have either a secondary or tertiary amide at the anomeric center and could be considered when designing bioactive molecules with carbohydrate scaffolds. The structural analysis was also carried out for related divalent secondary and tertiary glycosyl amides and these compounds display preferences similar to that of the monovalent compounds. The constrained divalent compounds have potential for promoting formation of clusters that will have restricted structure and thus have potential for novel studies of mechanisms of action of multivalent ligands. Possible applications of such compounds would be as scaffolds for the design and synthesis of ligands that will facilitate protein-protein or other receptor-receptor interactions. The affinity of restricted divalent (or higher order) ligands, designed to bind to proteins that recognize carbohydrates which would facilitate clustering and concomitantly promote protein-protein interactions, may be significantly higher than monovalent counterparts or multivalent ligands without these properties. This may be useful as a new approach in the development of therapeutics based on carbohydrates.